PANDANGAN FUQHA’ TERHADAP TAJDID an-NIKAH (Sebuah Ekplorasi Terhadap Fenomena Tajdid an-Nikah DI Desa Toket Kec. Proppo Kab. Pamekasan) - M Sahibudin M. Sahibuddin (Universitas Islam Madura, 2018)
From various views on tajdid an-nikah, both according to the previous fuqaha 'and community leaders / kyai as well as public acknowledgment of their experiences in performing tajdid an-nikah, researchers argue that 1) Tajdid an-marriage is not destructive in the first marriage contract, because he only repeated marriage licenses and only as a form of confirmation of his marriage. 2) Tajdid an-nikah may be carried out by a married couple to achieve domestic life full of love and affection and calmness in the face of his life. 3) Regarding the implementation of tajdid an-nikah as a form of reunification of marital relations damaged by the consequences of separation, for example, divorce before intercourse, khulu divorce (redeemed talak) divorce due to marriage annulled by facade) justified by law and their return justified by law, and divorce that has expired his iddah period. Where all of the above is justified by law. 4) Tajdid an-nikah activities with the reason that doubt has occurred in the marriage may not be done by the husband because he must first believe whether the divorce occurred or not. 6) The activities of tajdid an-nikah are also not justified by law if tajdid an-nikah is used as a guise to remarry with another woman who is not his wife who is lawful.